2015
DOI: 10.1021/nl5038825
|View full text |Cite
|
Sign up to set email alerts
|

Low B Field Magneto-Phonon Resonances in Single-Layer and Bilayer Graphene

Abstract: Many-body effects resulting from strong electron-electron and electron-phonon interactions play a significant role in graphene physics. We report on their manifestation in low B field magneto-phonon resonances in high-quality exfoliated single-layer and bilayer graphene encapsulated in hexagonal boron nitride. These resonances allow us to extract characteristic effective Fermi velocities, as high as 1.20 × 10(6) m/s, for the observed "dressed" Landau level transitions, as well as the broadening of the resonanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
63
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 42 publications
9
63
1
Order By: Relevance
“…We therefore conclude that the electron mobility in our sample is limited by intra-valley scattering events that are most likely caused by local strain fluctuations. This conclusion agrees with evidence we have from Raman experiments that high-mobility samples exhibit reduced strain fluctuations [42], as well as with recent studies on single-layer graphene, which also identified mechanical deformations as the main source of limiting mobility [43]. This in turn strongly suggests that the transport properties of both single-and bilayer graphene are hindered by the same physical mechanism.…”
supporting
confidence: 92%
“…We therefore conclude that the electron mobility in our sample is limited by intra-valley scattering events that are most likely caused by local strain fluctuations. This conclusion agrees with evidence we have from Raman experiments that high-mobility samples exhibit reduced strain fluctuations [42], as well as with recent studies on single-layer graphene, which also identified mechanical deformations as the main source of limiting mobility [43]. This in turn strongly suggests that the transport properties of both single-and bilayer graphene are hindered by the same physical mechanism.…”
supporting
confidence: 92%
“…[5][6][7] In particular, material stacks built around graphene (Gr) promise interesting electronic properties [8][9][10][11][12] and many possibilities for hosting high-quality devices. Different two-dimensional materials have been shown to be favorable substrates for graphene in such stacks.…”
mentioning
confidence: 99%
“…In particular, the small full width at half maximum (FWHM) of the graphene 2D line of around 17 cm −1 is an indication of the high crystal quality and local flatness of the encapsulated graphene sheet. 12,22 A scanning force microscopy (SFM) image of the Hall bar is shown in Figure 1e. Comparison with a scanning Raman microscopy image (Figure 1f), showing the intensity of the prominent Si Raman line at 520 cm −1 (see spectra in Figure 1d), reveals the high spatial resolution of our optical setup.…”
mentioning
confidence: 99%
“…In order to exclude other effects, the pseudomagnetic field must be uniform within the laser spot size in the confocal Raman spectroscopy experiment, which is exactly what we showed and discussed in this paper. By following the recent experiment of Neumann et al [21], where MPRs at low magnetic fields have been observed, we can estimate the experimental requirements for observing MPR shifts thanks to a tunable pseudomagnetic field. The most prominant MPR below 20 T is the so-called T 1 transistion at around 3.7 T, which results in an well resolved peak of the Raman G-line width as function of magnetic field.…”
Section: Experimental Implicationsmentioning
confidence: 99%
“…Therefore, strained graphene offers the unique opportunity to study the electronic properties of graphene at extreme (pseudo)magnetic field strengths. Alternatively, such systems could allow studies to the magneto-phonon resonance in Raman spectroscopy [21] or enable so-called valley-tronics [22][23][24]. Numerical work of strain fields in graphene is therefore of additional value, as it not only estimates the strength of the pseudomagnetic field, but also shows the uniformity of the generated pseudomagnetic field and its dependence on the lattice orientation with respect to the strain direction.…”
Section: Introductionmentioning
confidence: 99%